Manpower Constraints and Corporate Policies - Francesco D'Acunto; Michael Weber; Shuyao Yang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Manpower constraints are the pervasive lack of specialized high- and low-skill workers, irrespective of the wage firms might offer.
Keywords: J21; J31; J61; G31; G32; 330